2017
DOI: 10.1021/acs.langmuir.7b02257
|View full text |Cite
|
Sign up to set email alerts
|

Charging Poly(methyl Methacrylate) Latexes in Nonpolar Solvents: Effect of Particle Concentration

Abstract: The electrophoresis of a well-established model system of charged colloids in nonpolar solvents has been studied as a function of particle volume fraction at constant surfactant concentration. Dispersions of poly(12-hydroxystearic acid)-stabilized poly(methyl methacrylate) (PMMA) latexes in dodecane were prepared with added Aerosol OT surfactant as the charging agent. The electrophoretic mobility (μ) of the PMMA latexes is found to decrease with particle concentration. The particles are charged by a small mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…In this work, we report the first use of SANS measurements to study a system of PDMS-stabilized PMMA colloids. This extends the body of work using small-angle scattering to study PMMA latexes , that was previously limited to the PHSA-stabilizer. We do this by synthesizing PMMA latexes using covalently linked PDMS stabilizers to produce smaller colloids than previously reported , with a goal of accessing a size regime suitable for small-angle scattering measurements.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…In this work, we report the first use of SANS measurements to study a system of PDMS-stabilized PMMA colloids. This extends the body of work using small-angle scattering to study PMMA latexes , that was previously limited to the PHSA-stabilizer. We do this by synthesizing PMMA latexes using covalently linked PDMS stabilizers to produce smaller colloids than previously reported , with a goal of accessing a size regime suitable for small-angle scattering measurements.…”
Section: Introductionsupporting
confidence: 56%
“…Early interparticle scattering work confirmed that PHSA-stabilized PMMA nanoparticles in alkanes represented a good model hard-sphere system, even with bimodal size mixtures , and at high density. , More recently, it has been shown that through the addition of charge additives typically studied for electrophoretic display applications, similar PMMA nanoparticles display different structure at high densities because of their increased repulsion . Recently, their internal structure was also studied using small-angle neutron scattering (SANS), revealing the localization of absorbed surfactant charge-additives. …”
Section: Introductionmentioning
confidence: 99%
“…Millipore Ultrapure 18.2 MΩ·cm water was used throughout. The hydrophobic PMMA (polymethymethacrylate, stabilized by polyhydroxystearic acid; fluorescently labeled by DiIC 18 ) and the hydrophobic Sicastar silica (trimethylsilyl-coated) CPs used were spherical and fluorescently labeled and had diameters of ∼2.4 μm (PMMA) and 1.5 and 5–7 μm (silica). Nanoparticles (trimethylsilyl-coated silica, Sicastar), which are 250 nm in radius, have been employed as well.…”
Section: Methodsmentioning
confidence: 99%
“…where e 1 and e 2 are particle charges, ε r is the relative dielectric constant of the medium, ε 0 is the dielectric constant of vacuum, k B is the Boltzmann constant, and T is the temperature. For instance, λ B of water is 0.7 nm at 25 °C, while that of apolar medium is around 30 nm (such as dodecane's is 28 nm) [15][16][17] . On the one hand, this means that the capacitance of the electric double layer on particles in apolar media is small, which will result in the difficulty for particles to obtain the surface charge 18 .…”
Section: Introductionmentioning
confidence: 99%